2009
DOI: 10.1111/j.1753-6405.2009.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of musculoskeletal disorders in New Zealand nurses, postal workers and office workers

Abstract: Objectives: To describe the prevalence, characteristics and impact of musculoskeletal disorders (MSDs) in New Zealand nurses, postal workers and office workers. Methods: A postal survey asked participants about MSDs, (low back, neck, shoulder, elbow, wrist/hand or knee pain lasting longer than one day), and demographic, physical and psychosocial factors. Nurses were randomly selected from the Nursing Council database, postal workers from their employer's database and office workers from the 2005 electoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 18 publications
(36 reference statements)
6
65
3
4
Order By: Relevance
“…We also identified an overall prevalence of MSD as 97%, which was higher than the prevalence of MSD reported by previous studies, conducted at different settings. [11][12][13][14][15][16][17][18][19][20][21] Different body sites were taken into consideration in the analysis and we observed neck, shoulder, upper back and lower back as the most prominent areas which are affected, but among the four only two body sites, the neck and shoulder demonstrated statistical significance. However, according to Yan P et al (2017) the most commonly affected regions were lower back, neck,shoulder, and back, with an annual prevalence of 62.71%, 59.77%, 49.66%, and 39.50%, respectively.…”
Section: Prevalence Of Msdmentioning
confidence: 99%
“…We also identified an overall prevalence of MSD as 97%, which was higher than the prevalence of MSD reported by previous studies, conducted at different settings. [11][12][13][14][15][16][17][18][19][20][21] Different body sites were taken into consideration in the analysis and we observed neck, shoulder, upper back and lower back as the most prominent areas which are affected, but among the four only two body sites, the neck and shoulder demonstrated statistical significance. However, according to Yan P et al (2017) the most commonly affected regions were lower back, neck,shoulder, and back, with an annual prevalence of 62.71%, 59.77%, 49.66%, and 39.50%, respectively.…”
Section: Prevalence Of Msdmentioning
confidence: 99%
“…As an instance, in 2006, the number of PCs in the U.S., a developed country, was estimated to be about 240 million sets, and in Iran, a developing country, it was about 7.5 million sets [9]. According to research findings, a long-term use of computers can cause musculoskeletal problems in the upper-body parts, especially the neck, shoulders, arms, wrists and fingers [9,12]. Millions of computer users worldwide are susceptible to the risk of sore limbs.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and risk factors of these diseases in developing countries are being investigated [7]. The relevant risk factors are yet not completely known [9]. Previous studies have also revealed that sore neck and shoulder are significantly correlated with lower health state and quality of life [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barzideh, Choobineh, Tabatabaee, et al reported that physical job demands were associated with prevalence of MSDs among nurses [1]. Nursing work involves demanding physical activities such as lifting heavy objects, often in awkward postures, which sometimes entails forceful movements of the upper limbs [9]. Combination of compression, rotation, flexion and direct forces during patient transferring also increases the risk of injuries [10,11,12].…”
Section: Introductionmentioning
confidence: 99%